Exploration of the Word Formation Process in Online News Articles - Misbahillah, Al Khansa Nova; Jerau, Olivia Claresta Pratiwi; Indrawati, Fanny Khofifah (Universitas Pamulang, 2024)
Generation Z has become increasingly interested in seeking information on online platforms. As a result, numerous new terms begin to appear in society. New terms used in a language can be related to the word formation process, one of the morphological branches of linguistics. This study explored the process of word formation in online news articles, precisely the analysis section of opinion articles in the Jakarta Post online newspaper which ran from November 2023 to January 2024. In addition, this study aimed to provide several learning implications. The research design was descriptive qualitative because this study used discourse and morphological elements. Yule's (2017) theory was used to identify and classify the data into word formation categories. There were two findings of this study. First, the analysis revealed derivation as the most frequently used process in online news articles, accounting for 124 (33,42 %) and other processes such as multiple processes 80 (21,56 %), compounding 77 (20,75 %), acronym 64 (17,25 %), blending 7 (1,89 %), clipping 6 (1,62 %), borrowing 5 (1,35 %), conversion 6 (1,62 %), coinage 1 (0,27%), and back-formation 1 (0,27%). The second finding of this study revealed some important learning implications, such as increasing awareness of word structure, improving vocabulary, enhancing reading and writing skills, fostering creativity, and boosting cultural and digital literacy. Analyzing word formation processes helps language learners understand and decode complex texts, which supports overall literacy development. Therefore, language learners should engage in this activity to gain a thorough understanding of how language evolves and functions.